1962 Galerie Verriere 1982 : Perspectives - Permanences. - Fuoc, Henry; Verrière, Jacques; Galerie Verrière, Lyon (Lyon : Galerie Verrière, 1982)
Combet-Descombes, Pierre ; Chemay, Jacques ; Ethuin, Anne ; Guyon, Robert ; Jund, Bernard ; Artias, Philippe ; Valtat, Louis ; Avoscan, Ivan ; Braque, Georges ; Brassaï ; Klee, Paul ; Chéreau, Jean-Baptiste ; Cierniewski, Jean-Michel ; Cocteau, Jean ; Dali, Salvador ; Deswarte, Francis ; Domela, César ; Ferréol, Maurice ; Folon, Jean-Michel ; Fuchs, Ernst ; Gleizes, Albert ; Guérin, Armand ; Hayden, Henri ; Enri, Hel ; Hélion, Jean ; Léon, Jim ; Lapicque, Charles ; Fini, Leonor ; Lhote, André ; Loewer, Claude ; Man Ray ; Masson, Andre ; Perahim, Jules ; Jaguer, Edouard ; Jessemin, Aude ; Rivemale ; De Sanctis, Fabio ; Simoen, Gérard ; Roussille, Guy ; Salendre ; Schoendorff, Max ; Survage, Léopold ; Tàpies, Antoni ; Touques ; Vulliamy
biografie
Frans
boek